MENINGKATKAN KOMPETENSI LISTENING MENGGUNAKAN MEDIA FILM BOHEMIAN RHAPSODY PADA MAHASISWA PROGRAM STUDI S1 SASTRA INGGRIS UNIVERSITAS NGUDI WALUYO - Deswandito Dwi Saptanto; Tri Arie Bowo; Mochamad Rizqi Adhi Pratama (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2019)
Interesting learning methos are key points of successful teaching and learning activities.Hence, there should be a connectedness between lecturer, learning materials, and students.The use of flm as a learning medium is believed to be effective to improve learningoutcomes. In this study, the flm Bohemian Rhapsody was used to improve students'listening skills in analysing the conversations in the flm. The research method employedexperimental design involving pre-test, treatments (six times), and post-test. The researchresults showed that the given treatments is effective to improve students' skills in listeningespecially long conversation.